Days in the woods - Stone, A. Harris; Brooks, Dorian; Lindroth, David (Englewood Cliffs, N.J., Prentice-Hall, 1972)
An introduction to the plants, animals, and sounds one might encounter on a walk through the woods.
Keywords: Nature study -- Juvenile literature; Nature study